The taifa kingdoms (Leiden ; Boston)
xxiv, 729 sayfa
Keywords: “The 11th century has traditionally been regarded as a turning point in the evolution of medieval Iberia. The dismantling of the Umayyad Caliphate of Cordoba gave way to a process of political and territorial fragmentation that contributed to weakening Islamic power vis-a-vis the incipient Northern Christian kingdoms and ultimately leading up to the establishment of the Almoravid dynasty. The Taifa Kingdoms: Reconsidering 11th-century Iberia gathers contributions from a diverse group of Medieval Historians, Arabists, Art Historians and Archaeologist seeking to explore new approaches to understand one of the most complex and fascinating moments in al-Andalus. From political history, to socio-economic organization, and artistic and scientific activities, the book covers a wide range of topics and issues from fresh perspectives. Contributors Javier Albarran, Xavier Ballestin, Amira K. Bennison, Pascal Buresi, Elsa Cardoso, Carlos de Ayala, Carolina Domenech Belda, Maribel Fierro, Miquel Forcada, Alejandro Garcia-Sanjuan, Teresa Garulo, Adday Hernandez Lopez, Carlos Laliena, Eneko Lopez Martinez de Marigorta, Maria Marcos Cobaleda, Maria Antonia Martinez Nunez, Aurelien Montel, Julian Ortega, Alejandro Pelaez Martin, Victor Rabasco, Julio Samso, Bilal Sarr, Philippe Senac, and Bruna Soravia“ --